From Banned Bonds to Hungry Homes: Impacts of the COVID-19 pandemic and bans on associational life on food security among migrants on the margins - Bhanye, Johannes (The International Journal of Sociology of Agriculture and Food, 2023)
This paper examines the impacts that the COVID-19 pandemic and related bans on associational life had on the food security of migrants residing in informal settlements. Through ethnographic fieldwork at Lydiate informal settlement in the Norton peri-urban area, Zimbabwe – where Malawian migrants have established a unique home – the study reveals the transformative impacts of the pandemic on the livelihoods, food security, and everyday life of migrants. Lockdown measures disrupted crucial social support networks, including community organisations and informal associations that are essential to migrants’ and diasporas’ sense of belonging. The findings reveal a dramatic alteration in the lives of migrants at Lydiate, emphasising how limited access to these networks exacerbated food insecurity among a population already facing discrimination and exclusion from formal support systems. Beyond the immediate impacts of COVID-19 lockdowns on food security, pre-existing vulnerabilities (questionable legal status, lack of social safety nets, and resource constraints) also demonstrated the structural inequalities that shape the experiences of migrants in informal settlements. This complex array of challenges significantly influences food security outcomes among migrants on the margins during times of crisis. Understanding the impacts of bans on associational life and belonging among migrants necessitates a thoughtful approach to policy and practice. Policymakers and practitioners must consider the interconnectedness of social, economic, and psychological dimensions in the lives of migrants. Future research might usefully focus on how migrants find ‘informal or nimble ways of belonging’ to continue their lives even after bans on associational life in the community and beyond.